Effects of red ginseng extract on gut microbial distribution - Young Kyun Kim; Keun-Sang Yum (Journal of Ginseng Research, 2022)
Background: Red ginseng extract boosts immunity against inflammation and cancer in the human body. However, studies on the effects of red ginseng extract on the gut microbiome remain unexplored. Methods: In 2019, the positive effects and changes in the gut microbiome after administering 1 pack (3 g) of red ginseng extract per day to 53 adults aged 40 to 75 for 24 weeks were investigated. The gut microbial environment changes were qualitatively and quantitatively analyzed using next-generation sequencing and real-time polymerase chain reaction technology. Results: On comparing and analyzing alpha diversity and beta diversity, the microbial pattern showed significant differences (OTUs p = 0.003, chao1 p < 0.001, Bray-Curtis p = 0.001) before and after ingestion of red ginseng extract, indicating that gut microbial richness increased after ingestion. Moreover, after comparing and analyzing the gut microbiome's differences after red ginseng extract intake, significant differences were noted between three strains at the phylum level and among 57 strains at the genus level. Conclusion: This study proposes the potential use of red ginseng extract as a prebiotic after confirming its positive effects, including increasing gut microbiome richness, reducing harm to the gut microbiome, and increasing the number of some strains in the gut microbiome.